Mesopelagic community supported by epipelagic production in the western North Pacific Ocean based on stable isotope ratios of carbon and nitrogen. (April 2022) - Kobari, Toru; Nakamura, Rie; Noguchi Aita, Maki; Kitamura, Minoru
Abstract: We compared stable isotope ratios of carbon (δ 13 C) and nitrogen (δ 15 N) of epi- and mesopelagic mesozooplankton communities at subarctic (K2) and subtropical (S1) sites in the North Pacific Ocean to evaluate the relationship between mesopelagic communities and epipelagic production. Although δ 13 C and δ 15 N varied among the taxonomic groups, ostracods, carnivorous copepods, and chaetognaths tended to exhibit higher δ 13 C and δ 15 N than omnivorous copepods within the same layers. Mesozooplankton δ 13 C and δ 15 N were higher in the upper (200–500 m) and lower (500–1000 m) mesopelagic layers than in the epipelagic layer (0–150 m). δ 13 C and δ 15 N of mesozooplankton were positively correlated at all three depth-ranges at both sites. Although the slopes of linear regressions of δ 15 N vs. δ 13 C exhibited no significant differences among layers or between sites, the intercept was lower for mesozooplankton at S1. We attributed the similarity of slopes to common isotopic fractionation during protein synthesis among the different taxonomic groups, and the lower intercept to primary producers supported by recycled nutrients and atmospheric nitrogen fixation under the high thermal regime at S1. Our results further confirm earlier evidence that metabolic requirements of mesopelagic communities are supported by epipelagic production through the biological pump. Highlights: Subarctic and subtropical metazoans have higher δ 13 C and δ 15 N in deeper layers. Metazoan δ 15 N to δ 13 C are aligned regardless of the layers or sites. Regression intercepts of the δ 13 C-δ 15 N biplots are specific to the sites. Metazoan δ 13 C and δ 15 N represent biogeochemical processes at lower trophic levels.